2022
DOI: 10.7150/ijbs.74304
|View full text |Cite
|
Sign up to set email alerts
|

P2RY13 Exacerbates Intestinal Inflammation by Damaging the Intestinal Mucosal Barrier via Activating IL-6/STAT3 Pathway

Abstract: The pathogenesis of ulcerative colitis (UC) is unclear, while genetic factors have been confirmed to play an important role in its development. P2RY13 is a G protein-coupled receptor (GPCRs), which are involved in the pathogenesis of inflammation and immune disorders. According to GEO database analysis, we first observed that the expression of P2Y13 was increased in UC patients. Therefore, we sought to determine the role of P2Y13 in the development of colitis. Our data showed that P2RY13 was highly expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Further analysis showed that E. faecalis UA. Our previous study also found that the bacteria enriched the purine salvage-related proteins could decrease UA, 16 35 and IL-6 can increase the permeability of TJ proteins. For example, IL-6 leads to an approximately 3-4-fold increase in the transepithelial flux of urea.…”
Section: Discussionmentioning
confidence: 73%
“…Further analysis showed that E. faecalis UA. Our previous study also found that the bacteria enriched the purine salvage-related proteins could decrease UA, 16 35 and IL-6 can increase the permeability of TJ proteins. For example, IL-6 leads to an approximately 3-4-fold increase in the transepithelial flux of urea.…”
Section: Discussionmentioning
confidence: 73%
“…The product of the P2RY13 gene belongs to the G protein-coupled receptor family, a 354 amino acid-encoded gastrointestinal protein-coupled receptor that is involved in the pathogenesis of purine energy transfer pathways, cholesterol metabolism, inflammation and immune dysfunction mechanisms, mediating a variety of pathophysiological processes, such as apoptosis, autophagy, proliferation and metabolism ( 72 , 73 ). Many studies have shown that P2RY13 promotes apoptosis and increases the release of pro-inflammatory factors ( 74 , 75 ). In addition, P2RY13 is highly expressed in the inflamed intestinal tissue of ulcerative colitis patients ( 74 , 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that P2RY13 promotes apoptosis and increases the release of pro-inflammatory factors ( 74 , 75 ). In addition, P2RY13 is highly expressed in the inflamed intestinal tissue of ulcerative colitis patients ( 74 , 76 ). The above series of studies have shown that FGR , LCK , FYB1 , LY86 , and P2RY13 may play an important role in the dysfunction of immune cells such as macrophages, T lymphocytes, and B lymphocytes during the pathology of OB or PD.…”
Section: Discussionmentioning
confidence: 99%
“…P2RY13 a G protein‐coupled receptor that reacts to extracellular purine and pyrimidine nucleotides, negatively regulates adenylate cyclase activity 13 . Encoded by 354 amino acids (aa), it is linked to the development of inflammation and immune conditions 14 . While P2RY13 is particularly sensitive to ADP, it can be triggered by both ADP and ATP.…”
Section: Introductionmentioning
confidence: 99%
“…13 Encoded by 354 amino acids (aa), it is linked to the development of inflammation and immune conditions. 14 While P2RY13 is particularly sensitive to ADP, it can be triggered by both ADP and ATP. Research indicates a crucial function of P2RY13 in inflammation and immune imbalance.…”
mentioning
confidence: 99%